Gestão do capital intelectual e dos ativos intangíveis para geração de valor em instituições de ensino superior privadas no Brasil - Silva, Claudio Marcos Maciel da (2017)
The objective of this study was to investigate the strategic alignment process of private HEIs with knowledge — based mechanisms of intellectual capital and intangible assets. The specific objectives address the study of the effectiveness of theories on the strategy applied to the non-Brazilian higher education sector, the identification of the scenarios and the probable strategy for the private education in Brazilian higher education, as to identify which are the dimensions of intellectual capital Present in the private HEIs and how these are managed. The methodology used for the research lies in three steps. In the first, a study was carried out in scenarios of prospecting of higher education in order to ratify the existence of a dominant strategy in the segment. The next step of the research was the content analysis with teachers (called knowledge workers), in order to identify drivers of Intellectual Capital value. The last phase of the research was the study on the strategic alignment of private education institutions presented on the websites of private HEIs. The results point to the existence of a dominant strategy with predominance of Financial Capital and Structural Capital, and other emergencies, articulated by Human Capital and Relational Capital.